2009
DOI: 10.1111/j.1467-8535.2008.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Does regular online testing enhance student learning in the numerical sciences? Robust evidence from a large data set

Abstract: In recent years, online tools have increasingly contributed to both course delivery and assessment across various domains with mixed quantitative results. We examine the introduction of a regular online assessment tool ('e-quiz') delivered by the WebCT Vista content management system to a large first-year quantitative methods course at UNSW, Sydney (Australia). Unique aspects of this study include the quantitative (mathematical) nature of the online learning, the larger than usual sample size (n > 1500 in toto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 11 publications
6
83
0
5
Order By: Relevance
“…It was found that the scores of online homework assignments and final grade are strongly correlated in any of the groups. This result is in agreement with the existing literature (Varsavsky, 2004;Roth, Ivanchenko, & Record, 2008;Ruokokoski, 2009;Rasila, Majander, & Malinen, 2010;Angus & Watson, 2009;Huisman & Reedijk, 2012;Rivera, Ochoa, & Perez, 2013) and with the students' opinions gathered in survey.…”
Section: Discussion and Future Worksupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that the scores of online homework assignments and final grade are strongly correlated in any of the groups. This result is in agreement with the existing literature (Varsavsky, 2004;Roth, Ivanchenko, & Record, 2008;Ruokokoski, 2009;Rasila, Majander, & Malinen, 2010;Angus & Watson, 2009;Huisman & Reedijk, 2012;Rivera, Ochoa, & Perez, 2013) and with the students' opinions gathered in survey.…”
Section: Discussion and Future Worksupporting
confidence: 82%
“…With respect to the impact of e-assessments in mathematics the majority of the studies show that e-assessments with formative feedback contribute to student learning and improve student performance on the final course exam (Varsavsky, 2004;Roth, Ivanchenko, & Record, 2008;Ruokokoski, 2009;Rasila, Majander, & Malinen, 2010;Angus & Watson, 2009;Huisman & Reedijk, 2012;Rivera, Ochoa, & Perez, 2013.). However, there are also studies showing that online quizzes do not significantly improve student learning.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the quizzes was to ensure students came to class informed, thereby transforming class time from content-heavy didactic lectures to interaction-rich use of debate, discussion, modelling and practice of clinical skills. Using online quizzes in a similar way has been successful in improving student engagement and learning outcomes across a range of disciplines and blended learning contexts (Angus & Watson, 2009;Kibble, 2011;McKenzie et al, 2013;Peat & Franklin, 2002;Stull, Varnum, Ducette, Schiller, & Bernacki, 2011).…”
Section: Teaching Contextmentioning
confidence: 99%
“…Henly 2003) to mainly summative online tests (e.g. Marriott 2009), while Angus and Watson (2009) describe a model that combines formative with summative principles by allowing multiple attempts and using the best attempt for marking purposes. Automatically generated feedback may give information about whether an answer is correct or not, sometimes followed by in-class clarification of common misconceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%